Educational Quality Development for The Achievement to “Digital Island” - Tika, Setia; Puspitasari, Puspitasari (LSPR Institute of Communication & Business, 2021)
This paper aims to understand the Educational Quality Development for the achievement of “Digital Island“ a corporate social responsibility (CSR) implementation in Harapan Island, Indonesia. To build a digital Island need quality human resources, technology, expert english language, good infrastructure, good cooperation with the factory ,some foreign industry and good social culture. This study explains why must choose youths Harapan Island because in this island regularly every year held CSR from China National Offshore Oil Corporation (CNOOC SES Ltd). Based on the findings of the research, the following conclusions were made. In general, students of MAN 1 Harapan Island,Thousand Island are quite enthusiastic in participating in Future Orientation training activities. The implementation of tutoring takes place conducively. The results of the diagram percentage of the achievement of the competency of the try out results are 2 students with the highest score = 87 out of a total of 2 students who achieved a very good value range. Furthermore, 9% obtained a good range of values, 53% gained enough ranges, while the remaining 34% obtained a range of less values. With such results, all students are expected to be able to improve their motivation and learning efficiently and optimally referring to the results of a try out that is not satisfactory, the students must work harder in motivating themselves and further improve their fighting power and learning spirit.